THE EFFECT OF ELECTRONIC WORD OF MOUTH, MESSAGE SOURCE CREDIBILITY, INFORMATION QUALITY ON BRAND IMAGE AND PURCHASE INTENTION - Atika Atika; Andriani Kusumawati; Mohammad Iqbal (EKUITAS (Jurnal Ekonomi dan Keuangan), 2016)
This study is aimed to investigate the extent to which electronic word of mouth (eWOM) affects brand image and purchase intention. Further, other variables employed in this study are message source credibility and information quality. These variables are employed to explore the influence of eWOM on brand image and purchase intention by simultaneously involving message source credibility and information quality as independent variables. Message source credibility and information quality become important, because they can affect persuasion of customers. The research type is explanatory research with quantitative approach. The sampling technique used in this study was purposive sampling. The model was tested empirically using sample of 138 members of MIUI Indonesia Fansite. Analysis data technique in this study uses Generalized Structured Component Analysis (GSCA) to examine the effect of electronic word of mouth, message source credibility, information quality on brand image and purchase intention. Results showed that electronic word of mouth, message source credibility, information quality have positive and significant effect on brand image and purchase intention. Key words: electronic word of mouth; message source credibility; information; brand image; purchase intention